Hepatitis B e antigen and antibody activity in hepatitis B virus infection - Tiku, M.L.; Makhdoomi, G.M.; Beutner, K.R.; Nath, N.; Ogra, P.L. (The Journal of pediatrics, 1977)
Groups of institutionalized subjects, volunteer blood donors with serologic evidence of asymptomatic hepatitis B virus infection, and patients with acute type B viral hepatitis were studied for the presence of hepatitis B e antigen and antibody in a sequential manner over a period of two to three years. HB eAg was detected in 9.5% of institutionalized residents and volunteer blood donors and in 24% of patients with acute type B viral hepatitis. HB eAg positive subjects frequently had persistently elevated pyruvic glutamic transaminase levels in the serum. Anti HB e activity was observed in 26 to 32% of subjects positive for hepatitis B surface antigen. Long-term follow-up indicated that HB sAg positive subjects with anti HB e did not eventually become seronegative for HB sAg.